Availability and rationality of fixed dose combinations available in Kaduna, Nigeria - Auwal F; Dahiru MN; Abdu-Aguye SN (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: Fixed-dose drug combinations (FDCs), are combinations of two or more active drugs in a single dosage form. Despite the advantages obtained from the use of these agents, there is increasing evidence questioning the rationality of several FDCs found in pharmaceutical markets-especially those in developing countries like Nigeria. Objectives: To describe the availability of FDCs in drug retailing outlets located in Kaduna Nigeria, and to assess FDC registration status and inclusion on national and international essential medicines lists (EMLs). Rationality of selected FDCs was also assessed. Methods: A cross-sectional survey was carried out from June to September 2018 in 60 registered pharmacies and patent medicine shops selected through multi-stage sampling. A data collection form was used to obtain information on the generic names and strengths of the active ingredients of the FDCs, their country of manufacture and evidence of registration with the Nigerian drug regulatory agency. To assess rationality, a scoring rubric developed from earlier studies was used. Data collected was coded and entered into a Microsoft excel 2016 spreadsheet for analysis. Descriptive statistics (frequencies and percentages) were used to report the data collected. Results: FDCs encountered included 74 oral tablets/capsules, 52 oral liquids and 23 topical semi solids. Majority of the available FDCs were registered by Nigerian drug regulatory agency (91.5%), although only 8.5% and 6.5% in total were included on the Nigerian EML and the WHO model list respectively. Of the 99 FDCs assessed for rationality, 58 (58.6%) were found to be rational. Irrational FDCs included drugs acting on the respiratory tract (29.3%), analgesics (26.8%) and anti-infectives (22%). Conclusions: A wide variety of FDCs were available in the study area, even though not all of them were rational. There is an urgent need for policy makers within the country to develop better detailed guidelines for FDC registration.